Pengaruh pengungkapan sustainability report terhadap kinerja keuangan perusahaan infrastruktur yang terdaftar di bursa efek indonesia - Manisa, Dea Eka; Defung, F.; Kadafi, Muhammad Amin (FORUM EKONOMI, 2017)
Effect of Disclosure Sustainability Report on Return on Equity (ROE) on Infrastructure Company Listed in Indonesia Stock Exchange (BEI) in the period 2010-2014. Sustainability Report is a concept that companies have a responsibility towards customers, employees, shareholders, communities and the environment in all aspects of company operations. With the implementation of the sustainability report Sustainability report will have an impact on the sustainability of the company. Sustainability report is a non-financial report consists of six elements, namely economic performance, environmental, human rights, labor practices and decent work, social, and product responsibility. This study aims to examine the relationship between the financial sustainability report of an individual's performance on the financial performance of the company. Samples were 30 companies listed in Indonesia Stock Exchange during the period 2010-2014. The independent variable is the disclosure of economic performance, environmental, human rights, labor practices and decent work, social, and product responsibility. The independent variables were measured using an index of disclosure. Free sustainability report comes from the Global Reporting Initiative (GRI) is used as the basis for calculating the value of the index. The dependent variable is the Return on Equity (ROE) as a measure of financial performance. This study uses secondary data gathered from the company's site and the Indonesia Stock Exchange. The results showed that only the disclosure of social performance and disclosure responsibility performance products that affect the company's financial performance.Keywords: Sustainability Report, ROE, Global Reporting Initiative (GRI-index)